2014
DOI: 10.1183/09031936.00062714
|View full text |Cite
|
Sign up to set email alerts
|

Infantile respiratory syncytial virus and human rhinovirus infections: respective role in inception and persistence of wheezing

Abstract: There is evidence that respiratory viruses play a key role in the development and exacerbation of obstructive respiratory diseases in children. This review attempts to juxtapose the separate profiles and prototypes of pathogenenetic mechanisms represented by the two most common amongst such viruses: respiratory syncytial virus (RSV) and human rhinovirus (HRV).RSV represents the most common agent of severe airway disease in infants and young children, and is predominant in winter months. Large epidemiological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(168 citation statements)
references
References 140 publications
(233 reference statements)
4
158
2
4
Order By: Relevance
“…[11,12] However, whether this association is causal or reflects an underlying susceptibility to both early infection and asthma remains unclear. [11,13,31] It has been suggested that severe rhinovirus-induced infections may be a susceptibility marker for development of childhood asthma in predisposed children, rather than an inducer (causing asthma).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[11,12] However, whether this association is causal or reflects an underlying susceptibility to both early infection and asthma remains unclear. [11,13,31] It has been suggested that severe rhinovirus-induced infections may be a susceptibility marker for development of childhood asthma in predisposed children, rather than an inducer (causing asthma).…”
Section: Discussionmentioning
confidence: 99%
“…[11,[14][15][16][17] However, the exact role of early infections in the pathogenesis of asthma remains unclear. [11][12][13] Studies examining subgroups of patients with bronchiolitis generally classify children according to a limited number of characteristics (e.g., RSV-status, wheezing) or to a single dimension (e.g., severity score). Compared to this simple approach, the benefits of multidimensional approaches in addressing a heterogeneous disease (with regards to its etiology, pathobiology or treatments) have been demonstrated for other respiratory/allergic disorders, such as asthma, wheezing illness of childhood, or atopy.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Głównymi czynnikami wywołującymi pierwsze epizody świstów oddechowych u niemowląt i małych dzieci są wirusy -zwłaszcza RSV oraz rhinowirusy (RV) [13].…”
Section: Przebieg Naturalny Astmy Wczesnodziecięcejunclassified